Chronic copper exposure elicit neurotoxic responses in rat brain: Assessment of 8-hydroxy-2-deoxyguanosine activity, oxidative stress and neurobehavioral parameters - Kumar, Jayant; Sathua, Kshirod Bihari; Flora, S. J. S. (Cellular and Molecular Biology, 2019)
Copper (Cu), one of the essential transition metal acts as a prosthetic group for variety of proteins and metalloenzymes. However, it may be hazardous when administered in excess. Copper induced memory impairment and progression of neurodegenerative diseases have not yet been fully elucidated. The aim of the present study was to investigate the effect of exposure to copper sulphate (10mg/kg and 20mg/kg body weight, daily for 16 weeks) on brain copper concentration, few biochemical parameters indicative of oxidative stress and on different neurobehavioral functions in male Sprague Dawley rats. Copper-administered animals showed significant increase in brain copper concentration and a depleted Ceruloplasmin level. Different neurobehavioral studies revealed impaired memory and motor coordination in copper exposed rat. Spontaneous locomotors activity and depression symptoms were also noted in copper intoxicated rats. 8-hydroxy-2' -deoxyguanosine (8-OHdG) level, one of the predominant forms of free radical-induced oxidative lesions, and has been widely used as a biomarker for oxidative stress, increased in copper treated group. Copper induced oxidative stress in the brain was also evident from the increased lipid per oxidation (LPO) and nitrite level, depletion of reduced glutathione (GSH), and reduced activities of the antioxidant enzymes such as superoxide dismutase (SOD), and catalase. The present study thus suggests a significant correlation between copper induced oxidative stress and changes in neurobehavioral function in rats. The changes were more pronounced in animals exposed to a higher dose of copper (20mg/kg) than the lower dose.